(untitled) (مجلة إحالات, 2026)
The research is interested in presenting an important aspect of the textual linguistic, focusing its attention exactly the concept substitution; witch its process that take place with in the text, falls in the grammatical cohesion, is a parallel function with other foundry methods such as reference, ellipsis and recurrence, so substitution is important technique in the cohesion of the texts; it may not be enough alone to archive consistency but it is one of the most important means of contributing the part of text and discrimination it from no text.